2023
DOI: 10.1097/mnm.0000000000001678
|View full text |Cite
|
Sign up to set email alerts
|

Optimising cylinder model dimensions for VARSKIN to simulate a droplet of radionuclide skin contamination using Geant4 Monte Carlo code

Abstract: Aim VARSKIN provides a convenient way of calculating skin dose from predefined geometries but the models are limited to concentric shapes such as discs, cylinders and point sources. The aim of this article is to use the Geant4 Monte Carlo code to independently compare the cylindrical geometries available in VARSKIN to more realistic droplet models obtained from photography. It may then be possible to recommend an appropriate cylinder model that can be used to represent a droplet within acceptable accuracy. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…When comparing the dose rate and associated dose for the 10 µl droplet model measured in this work with results from Amato et al (2018), Delacroix et al (2002) and James et al (2023), although doses were found to be lower with the smaller droplet models, significant differences were found between the two 10 µl droplet models. For example, the skin dose for the 10 µl droplet model used in this work was 282 mSv for 18 F-FDG compared with 116 mSv measured by James et al (2023).…”
Section: Implications For Skin-dose Estimationssupporting
confidence: 53%
See 4 more Smart Citations
“…When comparing the dose rate and associated dose for the 10 µl droplet model measured in this work with results from Amato et al (2018), Delacroix et al (2002) and James et al (2023), although doses were found to be lower with the smaller droplet models, significant differences were found between the two 10 µl droplet models. For example, the skin dose for the 10 µl droplet model used in this work was 282 mSv for 18 F-FDG compared with 116 mSv measured by James et al (2023).…”
Section: Implications For Skin-dose Estimationssupporting
confidence: 53%
“…The impact on the skin dose for a reduced droplet volume of 10 µl, using the droplet dimensions measured in this work, was evaluated with Monte Carlo simulations. Figure 4 compares the dimensions of the droplet model used with the 10 µl droplet model proposed by James et al (2023) and the 50 µl droplet model adopted by Amato et al (2018) and Delacroix et al (2002).…”
Section: Monte Carlo Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations